1996
DOI: 10.1111/j.1440-1754.1996.tb01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated schedule of hepatitis B vaccination in high‐risk youth

Abstract: High-risk youth can be immunized against hepatitis B successfully using an accelerated schedule, but compliance is difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Various studies concluded that a rapid vaccination scheme gave similar results with a traditional vaccination scheme, and anti-HBs response was maintained for at least 1 year [19, 20]. In our study, all cases administered a rapid vaccination scheme had developed a protective anti-HBs response at the end of month 1, while only five subjects in the group administered a traditional vaccination scheme had developed a protective anti-HBs response at the end of month 1.…”
Section: Discussionsupporting
confidence: 62%
“…Various studies concluded that a rapid vaccination scheme gave similar results with a traditional vaccination scheme, and anti-HBs response was maintained for at least 1 year [19, 20]. In our study, all cases administered a rapid vaccination scheme had developed a protective anti-HBs response at the end of month 1, while only five subjects in the group administered a traditional vaccination scheme had developed a protective anti-HBs response at the end of month 1.…”
Section: Discussionsupporting
confidence: 62%
“…Based on this finding, the authors 'strongly recommend against the 0-1-2 schedule for drug user patients'. Although most, but not all (Wilkinson et al 1996), studies indicate that the longer the interval between the second and third vaccine doses, the greater the seroresponse, the differences in seroresponse (solely on account of differences in vaccine schedule) determined by the authors are much higher than the relatively modest differences determined by fellow workers. For example, a New South Wales study of 455 inmates vaccinated using the 0-1-2 vaccination schedule and a 20 mg/dose vaccine showed a seroresponse rate of 85% (Awofeso 2002) compared with 89% among healthy adult volunteers using the same schedule (Smith- Kline Beecham 1999).…”
Section: Managerial Considerations In Implementing Hepatitis B Vaccinmentioning
confidence: 79%
“…In young drug-using populations, such barriers include access to health services, 17 cost of vaccine, 9 vaccination setting, 18 and duration of the vaccination course. 19 Thus, the removal of structural barriers in this project through proactive recruiting of at-risk youth (including non-IDUs), removing vaccination costs, shortening the time course of the vaccination schedule, and providing follow-up and reminder services, clearly assisted in the high level of completed vaccinations. In addition, the removal of attitudinal barriers, such…”
Section: Discussionmentioning
confidence: 99%